Synthesis and evaluation of an orally available "Y"-shaped biaryl peroxisome proliferator-activated receptor δ agonist. Issue 15 (15th August 2018) - Kim, Dong-Su; Lee, Jaehwan; Londhe, Ashwini M.; Kadayat, Tara Man; Joo, Jeongmin; Hwang, Hayoung; Kim, Kyung-Hee; Pae, Ae Nim; Chin, Jungwook; Cho, Sung Jin; Kang, Heonjoong
Graphical abstract: Abstract: In this study, we designed and synthesized several novel "Y"-shaped biaryl PPARδ agonists. Structure-activity relationship (SAR) studies demonstrated that compound3a was the most active agonist with an EC50 of 2.6 nM. We also synthesized and evaluated enantiospecific R and S isomers of compound3a to confirm that R isomer (EC50 = 0.7 nM) shows much more potent activity than S isomer (EC50 = 6.1 nM). Molecular docking studies between the PPAR ligand binding domain and enantiospecific R and S isomers of compound3a were performed. In vitro absorption, distribution, metabolism, excretion, and toxicity (ADMET) and in vivo PK profiles show that compound3a possesses superior drug-like properties including good bioavailability. Our overall results clearly demonstrate that this orally administrable PPARδ agonist3a is a viable drug candidate for the treatment of various PPARδ-related disorders.